Successful pharmaceutical-grade streptozotocin (STZ)-induced hyperglycemia in a conscious tethered baboon (Papio hamadryas) model - Frost, Patrice A.; Chen, Shuyuan; Mezzles, Marguerite J.; Voruganti, Venkata Saroja; Nava González, Edna Judith; Arriaga Cazares, Hector E.; Freed, Katy A.; Comuzzie, Anthony G.; DeFronzo, Ralph A.; Kent, Jack W.; Grayburn, Paul A.; Bastarrachea, Raúl A. (2015)
Background Non-human primate (NHP) diabetic models using chemical ablation of b-cells with STZ have been achieved by several research groups. Chemotherapeutic STZ could lead to serious adverse events including nephrotoxicity, hepatotoxicity, and mortality. Methods We implemented a comprehensive therapeutic strategy that included the tether system, permanent indwelling catheter implants, an aggressive hydration protocol, management for pain with IV nubain and anxiety with IV midazolam, moment-by-moment monitoring of glucose levels post-STZ administration, and continuous intravenous insulin therapy. Results A triphasic response in blood glucose after STZ administration was fully characterized. A dangerous hypoglycemic phase was also detected in all baboons. Other significant findings were hyperglycemia associated with low levels of plasma leptin, insulin and C-peptide concentrations, hyperglucagonemia, and elevated non-esterified fatty acids (NEFA) concentrations. Conclusions We successfully induced frank diabetes by IV administering a single dose of pharmaceutical-grade STZ safely and without adverse events in conscious tethered baboons.